THE EFFECT OF LEARNING INTEREST AND FAMILY ENVIRONMENT ON LEARNING DIFFICULTIES IN ACCOUNTING MAJOR 41 STATE VOCATIONAL HIGH SCHOOL JAKARTA. - Rahayu, Tika; Sumiati, Ati; Fauzi, Achmad (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2020)
This study aims to determine the impact of learning interest and family environment on learningdifficulties in accounting major of 41 state vocational high school Jakarta. the population ofthis study was 143 students. The sampling technique uses proportional random sampling to obtain asample of 105 students. Test requirements analysis is done, the data are expressed in normal and lineardistribution. Based on the analysis of the results of the study concluded that partially negative and notsignificant, and negative and significant effect (th1: -0,797; th2: -2,261 each < ttabel; 1,983). whilesimultaneously obtained Fcount (3,127) > Ftable (3,08) it can be concluded that the variables of learning interest and family environment have a positive and significant effect on learning difficulties by obtaininga multiple correlation coefficient of 0,465 and a coefficient of determination of 46,5%.